2013
DOI: 10.1080/13698575.2013.846302
|View full text |Cite
|
Sign up to set email alerts
|

Time frames and self-hurting: that was then, this is now

Abstract: In this article, we explore the different time frames through which 25 adults who have used non-suicidal self-hurting throughout their lives evaluate their experiences. Participants in the study on which this article is based were drawn from a non-clinical population recruited mainly through dedicated websites. All were interviewed in 2008 in South London. The participants all used time frames to structure their narratives about their use of self-hurting. Short time frames placed around the act of self-hurting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…The episodic nature of bipolar disorder brings out the importance of time when considering risks and uncertainties in clinical encounters (see, Alaszewski & Brown, 2016;Brown & de Graaf, 2013;Juhila et al, 2015;Klingemann, 2000;West et al, 2013). The onset of a serious illness can be interpreted as a disruption in the patient's everyday life, normality and biography (Alaszewski & Brown, 2016;Bury, 1982).…”
Section: Uncertainty Work and Timementioning
confidence: 99%
See 1 more Smart Citation
“…The episodic nature of bipolar disorder brings out the importance of time when considering risks and uncertainties in clinical encounters (see, Alaszewski & Brown, 2016;Brown & de Graaf, 2013;Juhila et al, 2015;Klingemann, 2000;West et al, 2013). The onset of a serious illness can be interpreted as a disruption in the patient's everyday life, normality and biography (Alaszewski & Brown, 2016;Bury, 1982).…”
Section: Uncertainty Work and Timementioning
confidence: 99%
“…Through the analysis, I show how temporality is essential in this practical labour of professionals and patients. The uncertainty work in clinical encounters is structured by two different time frames: clinical time and experienced time (see, Alaszewski & Brown, 2016;Brown & de Graaf, 2013;Juhila, Gunther, & Raitakari, 2015;Klingemann, 2000;West, Newton, & Barton-Back, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Narrative can create order to these experiences and events. West et al (2013) research exploring the narratives of people who 'self-hurt' showed the importance of temporality in framing the experience. For many participants, the past framed the appearance of the present, though crucially this was past lived experiences as narrated by the individual in which their biographical experience gave meaning to their present actions of self-hurt.…”
Section: Temporalmentioning
confidence: 99%
“…One article was hastily reoriented so that it could be published in the time special issue because the writers had missed the earlier deadline for papers on risk categorisation! The same project, investigating the accounts of their actions given by people who selfharm, was drawn on in relation to both the value (Barton-Breck and and time-framing (West, Newton and Barton-Breck, 2013) issues.…”
Section: The 'Lens Of Risk' Special Issue Seriesmentioning
confidence: 99%
“…However, we ended up with sufficient material for a double special issue. The published papers covered: home drinking in relation to concerns about the present and future (Foster and Heyman, 2013); the decision-making of older women about when to become pregnant (Locke and Budds, 2013); constructions of their futures by patients with advanced cancer (Brown and De Graaf, 2013); the temporal considerations of individuals who self-harm (West, Newton and Barton-Breck, 2013); and accounts of their time management given by patients who develop malignant melanoma (Topping, Nkosana-Nyawata and Heyman, 2013). The original call for papers referred to 'time-framing', drawing attention to the propensity of policy-makers, healthcare professionals and public to set temporal horizons beyond which risk assessment is not considered, as with the convention of assessing five-year survival for cancer treatments.…”
Section: The 'Lens Of Risk' Special Issue Seriesmentioning
confidence: 99%